Fairness and Managerial Rights in Canadian Arbitral Jurisprudence - Fisher, E.G.; Sherwood, L.M. (Relations industrielles / Industrial Relations, 1984)
This paper examines the duty of fairness as applied to management's rights under collective agreements in common law jurisdictions and concludes from recent arbitral and judicial decisions that it is somewhat of a dead issue, although clarification may be required.